اتجاهات مدرسي اللغة العربية في المدارس الأهلية نحو استخدام التعليم الالكتروني في ذي قار - عودة، مشتاق فاخر ضيدان; كاظم، علاء جبار (جامعة ذي قار - كلية التربية للعلوم الإنسانية, 2018)
study aims to identify the trends of Arabic teachers in private schools to use E learning in DhiQar The study uses a descriptive analytical approach because it is suitable for study variables . The people of this study are Arabic language teachers of the secondary stage in private schools in the DhiQar Education Department By 100%, a group of teachers from private schools was selected in the Department of Education in DhiQar The number of people from this study reached (90) Teachers (male and female) for the academic year2016\2017 The Two researchers prepared and distributed the study tool, which is the questionnaire on the people of this study, and 85 questionnaires were retrieved (94.5) After doing the statistical analysis this study revealed : •There are neutral trends for language teachers in private secondary schools in the DhiQar Education Department to use e-learning •At the level of statistical significance (0.05=a), there were no differences with statistical significance between trends teachers in private secondary schools in the DhiQar Education Department to use e-learning Under the variables (gender, academic qualification, and teaching experience).
هدفت هذه الدراسة التعرف إلى اتجاهات مدرسي اللغة العربية في المدارس الأهلية نحو استخدام التعليم الإلكتروني في ذي قار. وقد استخدمت الدراسة المنهج الوصفي التحليلي لملائمة المتغيرات الدراسة، وتكون مجتمع الدراسة من مدرسي اللغة العربية للمرحلة الثانوية في المدارس الأهلية في مديرية تربية الناصرية، وتم اختيار عينة المدرسين من المدارس الأهلية في مديرية تربية الناصرية بنسبة 100% ليبلغ عدد أفراد مجتمع الدراسة (90) مدرسا ومدرسة للعام الدراسي 2017/2016 ، وقد اعد الباحثان أداة الدراسة وهي الاستبانة وجرى توزيعها على أفراد عينة الدراسة واسترجع منها (85) استبانة بنسبة. (94.5) وبعد إجراء عملية التحليل الإحصائي توصلت الدراسة إلى ما يلي: وجود اتجاهات محايدة لدى مدرسي اللغة العربية في المدارس الثانوية الأهلية في مديرية تربية الناصرية نحو استخدام التعليم الالكتروني. عدم وجود فروق ذات دلالة إحصائية عند مستوى الدلالة الإحصائية (α=0.05) بين متوسطات اتجاهات مدرسي اللغة العربية في المدارس الثانوية الأهلية في مديرية تربية الناصرية نحو استخدام التعليم الإلكتروني تعزى لمتغيرات (الجنس، والمؤهل العلمي، والخبرة التدريسية).
Keywords: الاتجاهات -- تكنولوجيا التعليم -- التعليم الالكتروني -- المدارس الأهلية -- التحصيل العلمى -- مدرسو اللغة العربية